Digital life storybooks for people with dementia living in care homes: an evaluation - Subramaniam P (Dove Medical Press, 2016)
Ponnusamy Subramaniam,1 Bob Woods2 1Health Psychology Programme, University Kebangsaan Malaysia, Kuala Lumpur, Malaysia; 2Dementia Services Development Centre Wales, Bangor University, Bangor, Gwynedd, UK Background and aim: There is increasing interest in using information and communication technology to help older adults with dementia to engage in reminiscence work. Now, the feasibility of such approaches is beginning to be established. The purpose of this study was to establish an evidence-base for the acceptability and efficacy of using multimedia digital life storybooks with people with dementia in care homes, in comparison with conventional life storybooks, taking into account the perspectives of people with dementia, their relatives, and care staff.Methods: Participatory design was used to create a life story movie based on a previously completed conventional life storybook with six older adults with dementia (four females; mean age 82 years). Relatives were involved in helping the participant to provide additional information and materials for the digital life storybook. In this multiple case study design, both quantitative and qualitative approaches were used. For quantitative purposes, a set of questionnaires that had been completed three times before and after the conventional life storybook was developed were repeated 4 weeks after the life story movie was completed. Semistructured interview questions were designed to collect feedback from participants, relatives, and care staff.Results: The result indicated that five of the six participants showed additional improvement in measures of quality of life and autobiographical memory. All participants showed improvement or stability in depression scores. Thematic analysis showed that, participants, relatives, and care home staff viewed digital life storybooks as a very useful tool triggering memories and (largely) positive emotions. Participants’ case vignettes were presented to document the impact of digital life storybook. Keywords: care homes, dementia, ICT, life storybook, reminiscence